Toxicological evaluation of the flavour ingredient 4-amino-5-(3-(isopropylamino)-2, 2-dimethyl-3-oxopropoxy)-2-methylquinoline-3-carboxylic acid. (2015) - Arthur, Amy J.; Karanewsky, Donald S.; Liu, Hanghui; Chi, Bert; Markison, Stacy
Abstract: A toxicological evaluation of 4-amino-5-(3-(isopropylamino)-2, 2-dimethyl-3-oxopropoxy)-2-methylquinoline-3-carboxylic acid(S9632; CAS 1359963-68-0), a flavour with modifying properties, was completed for the purpose of assessing its safety for use in food and beverage applications. No Phase I biotransformations of S9632 were observed in rat or human microsomes in vitro, and in rat pharmacokinetic studies, the compound was poorly orally bioavailable and rapidly eliminated. S9632 was not found to be mutagenic or clastogenic in vitro, and did not induce micronuclei or indicate interactions with the mitotic spindle in an in vivo mouse micronucleus assay at oral doses up to 2000 mg/kg. In subchronic oral toxicity studies in rats, the NOEL was 100 mg/kg/day (highest dose tested) for S9632 when administered as a food ad-mix for 90 consecutive days. Furthermore, S9632 demonstrated a lack of maternal toxicity, as well as adverse effects on fetal morphology at the highest dose tested, providing a NOEL of 1000 mg/kg/day for both maternal toxicity and embryo/fetal development when administered orally during gestation to pregnant rats.